Optimalization of the Use of Intellectual Property Rights Through Acceleration of P5KWU Modules Base on Local Requirements for Students of Seve-City Semarang - Santoso, Jarot Tri Bowo; Miftahunnajah, Nimas Aulia Pambajeng; Margunani; Dahlan, Tri Andari; Devitrisia, Naim (Jurnal Pengabdian Masyarakat, 2025)
Purpose: This program aims to help teachers overcome challenges in developing modules that align with student characteristics and the local environment while improving their understanding of Intellectual Property Rights (IPR). It also seeks to integrate local wisdom into learning and strengthen UNNES' role in entrepreneurship education in Semarang. Method: The program utilizes workshops, technical guidance, and periodic mentoring to equip teachers with the necessary skills for module development and IPR knowledge. Practical Applications: By incorporating local wisdom, the program has made educational modules more relevant and engaging for students, enhancing their learning experience and better reflecting the regional context Conclusion: The program successfully addressed teachers' difficulties in module creation, improved their IPR understanding, and strengthened UNNES' leadership in entrepreneurship education, making a significant impact on the educational landscape in Semarang.